2013
DOI: 10.1037/a0028276
|View full text |Cite
|
Sign up to set email alerts
|

Perceived partner responsiveness moderates the association between received emotional support and all-cause mortality.

Abstract: Objective: The aim of this study was to investigate whether perceived partner responsiveness (PPR) moderates the association between received partner emotional support (RPES) and all-cause mortality in a national U.S. sample. Method: Data were from the National Survey of Midlife Development in the United States, a national probability survey of health and aging. Participants included respondents who were married or cohabiting with a romantic partner. Results: Hierarchical logistic regression analyses indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 26 publications
7
95
0
3
Order By: Relevance
“…Consistent with the large and growing literature on the benefits of perceived responsiveness (Laurenceau et al, 1998;Maisel & Gable, 2009;Selcuk & Ong, 2013;Selcuk et al, 2016), we found evidence suggesting benefits of perceived responsiveness for sleep (and marginally for subjective health), positive and negative emotions, and subjective coping.…”
Section: The Benefits Of a Responsive Partnersupporting
confidence: 77%
See 2 more Smart Citations
“…Consistent with the large and growing literature on the benefits of perceived responsiveness (Laurenceau et al, 1998;Maisel & Gable, 2009;Selcuk & Ong, 2013;Selcuk et al, 2016), we found evidence suggesting benefits of perceived responsiveness for sleep (and marginally for subjective health), positive and negative emotions, and subjective coping.…”
Section: The Benefits Of a Responsive Partnersupporting
confidence: 77%
“…Regarding the relationship between perceived responsiveness and people's health and well-being while they await uncertain news, accumulating evidence supports the benefits of perceived responsiveness for lowering distress and improving physical health and sleep quality (Selcuk & Ong, 2013;Selcuk et al, 2016). Therefore, we anticipated that the well-established benefits of perceived responsiveness would extend to waiting periods as well.…”
Section: Health and Well-being (Question B)mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, research has shown that received social support that is not responsive to individuals' basic and circumstantial needs is often associated with poorer healthrelated outcomes (Ibarra-Rovillard and Kuiper 2011;Maisel and Gable 2009;Selcuk and Ong 2013). Being able to assess whether older adults prefer receiving social support for functional autonomy or dependence when in pain would contribute to increase formal social support responsiveness.…”
Section: Formal Social Support For Functional Autonomy and Dependencementioning
confidence: 99%
“…For instance, among patients undergoing knee surgery, partner responsiveness during recovery predicted fewer knee limitations 3 months later (Khan, et al, 2009). Recently, it was shown that perceived partner responsiveness interacted with social support to predict longevity in a large sample of married and cohabitating couples from the National Survey of Midlife Development in the United States (MIDUS) study (Selcuk & Ong, 2013). We propose that a critical pathway through which perceived partner responsiveness positively impacts health and longevity is through its effect on the hypothalamic-pituitary-adrenal (HPA) axis and its hormonal product, cortisol.…”
mentioning
confidence: 99%